Sustainable solvent selection for the manufacture of methylammonium lead triiodide (MAPbI3) perovskite solar cells. Issue 6 (12th March 2021) - Doolin, Alexander James; Charles, Rhys Gareth; De Castro, Catherine S. P.; Rodriguez, Rodrigo Garcia; Péan, Emmanuel Vincent; Patidar, Rahul; Dunlop, Tom; Charbonneau, Cecile; Watson, Trystan; Davies, Matthew Lloyd
Abstract : An approach for screening solvent systems for PSCs to substitute REACH restricted DMF with no loss in device performance. Abstract : Perovskite solar cells have emerged as a promising and highly efficient solar technology. Despite efficiencies continuing to climb, the prospect of industrial manufacture is in part hampered by concerns regarding the safety and sustainability of the solvents used in lab scale manufacture. In this paper, we aim to present a methodology for green solvent selection informed by EHS considerations from the CHEM-21 solvent guide for successful methylammonium lead triiodide (MAPbI3 ) precursor dissolution. Through the use of this methodology we present a N, N -dimethylformamide (DMF)-free alternative solvent system for deposition of MAPbI3 precursors (MAI and PbI2 ) consisting of dimethyl sulfoxide (DMSO), dimethylpropyleneurea (DMPU), 2-methyltetrahydrofuran (2-MeTHF) and ethanol (EtOH). We have investigated 3 candidate solutions with slightly different compositions of these four solvents, all of which produce dense, uniform and pinhole-free perovskite films via spin coating. All three candidate solutions (A–C) match the average device efficiencies of the DMF/DMSO control devices (12.4%) with candidate A, which consists of 40% DMSO, 30% DMPU, 20% 2-MeTHF and 10% EtOH (vol%), producing a champion PCE of 16.1% compared to 16.2% for DMF/DMSO (80/20 vol%). Perovskite films cast from the three candidate solutions show improved crystallinity, higher fluorescence emission, and improved crystal size uniformity than those cast from DMF/DMSO. This work aims to: highlight the key solvent parameters which determine effective MAPbI3 precursor dissolution; provide a set of criteria for appropriate alternative solvent selection; and demonstrate the application of green chemistry principles to solvent selection for perovskite photovoltaic manufacturing.